Negara-negara Gagal di Pulau Jawa (Study Archeologi Hukum tentang Sistem Hukum yang Meruntuhkan Negara) - Pandoman, Agus (CV. Kurnia Grup, 2025)
The monumental ruins left behind by the royal states on the island of Java in the past gripped me with the romantic appeal of my ancestors, who were born and lived on this island, but who became citizens of which kingdom, because the nation and state had collapsed and disappeared. I am drawn to the beauty of the ruins of buildings or the remaining walls of monumental structures, which are often spectacular and gripping, and the mysteries they present. Are we, as we are now, part of those ruins and all that remains are the monuments to the past glory of the State. The destruction of the Majapahit Kingdom, the Demak Kingdom, the Mataram Kingdom, the Kediri Kingdom, the Singasari Kingdom, the Daha Kingdom, most of the royal sites can be said not to be a state and not a government that has majesty and political entity. Analysis of this article, using a legal anthropology approach, with the hypothesis that the legal system built with the ambition of power, bringing down the nation and state, legal culture without certainty, justice, and order leads to the collapse of the state. The glory of the nation and state has been lost. Analysis of research using the Anthropology approach shows that the collapse of the legal system, eliminates the nation and state.